Exploring the potential of nutraceutical to combat gliomas: focus on mIDH2 protein - Murali, Poornimaa; Karuppasamy, Ramanathan (Frontiers in Physics, 2024)
Somatic transformations in the key catalytic residues of the Isocitrate Dehydrogenase (IDH) enzyme assist in the onset of distinct malignancies including glioma. Currently, enasidenib is the FDA-approved drug used to target IDH2 protein. However, the use of enasidenib as a plausible mIDH2 inhibitor is constrained by poor brain penetrating capability and dose-limiting toxicity. Thus, the present study aimed to explore the potential of nutraceuticals to synergistically elevate the efficacy of the existing drugs available for glioma management. The binding affinity and free energy of the nutraceuticals were evaluated using molecular docking and MM-GBSA analysis. The resultant 14 compounds were subjected to machine learning-based rescoring strategies to distinguish binders from nonbinders. The pharmacokinetic and toxicity analysis was also implemented alongside virtual cell line assay. The results of our study identified DB14002 (D-alpha-Tocopherol acetate, analog of Vitamin E) as the potential hit compound with appreciable binding affinity, brain penetrating capability and antineoplastic activity against glioma cell lines. In the end, the conformational stability and dynamic characteristics of DB14002 were examined for a stipulated time frame of 250ns. Indeed, the outcomes of our study culminate the use of DB14002 as a synergistic drug-like candidate which could be translated as a plausible inhibitor of mIDH2 in the forthcoming years.